2013
DOI: 10.1039/c3cc43463j
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium catalyzed hydroaminoalkylation of isoprene via transfer hydrogenation: byproduct-free prenylation of hydantoins

Abstract: The ruthenium catalyst derived from Ru3(CO)12 and triphos [Ph2P(CH2CH2PPh2)2] promotes the direct C–C coupling of isoprene with aryl substituted hydantoins 1a–1f at the diene C4-position to furnish products of n-prenylation 2a–2f. A mechanism involving hydantoin dehydrogenation followed by diene-imine oxidative coupling to furnish a transient aza-ruthencyclopentene is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
(7 reference statements)
1
30
0
Order By: Relevance
“…In contrast, the development of corresponding late transition metal catalyzed amine C-H functionalizations has proven challenging. 92–94 Indeed, with the exception of the present authors work, 9599 all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. 100108 In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti -diastereoselectivity (Scheme 18).…”
Section: Hydroaminoalkylationmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast, the development of corresponding late transition metal catalyzed amine C-H functionalizations has proven challenging. 92–94 Indeed, with the exception of the present authors work, 9599 all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. 100108 In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti -diastereoselectivity (Scheme 18).…”
Section: Hydroaminoalkylationmentioning
confidence: 68%
“…99 Presently, transformations of this type are restricted to the hydroaminoalkylation of isoprene with aryl substituted hydantoins. The catalytic mechanism involves hydrogenolytic cleavage of the azaruthenacyclopentane intermediate through hydrogen transfer from the hydantoin reactant, which releases product and regenerates the requisite imine for oxidative coupling.…”
Section: Hydroaminoalkylationmentioning
confidence: 99%
“…In contrast, the development of corresponding late transition metal catalyzed amine C-H functionalizations has proven challenging. [92][93][94] Indeed, with the exception of the present authors work, [95][96][97][98][99] all other late transition metal catalyzed hydroaminoalkylations require pyridyl directing groups in combination with mono-olefin reactants. [100][101][102][103][104][105][106][107][108] In a significant departure from prior art, it was found that ruthenium catalyzed hydrogen transfer from 4-aminobutanol to 1-substituted-1,3-dienes results in the generation of dihydropyrrole-allylruthenium pairs, which combine to form products of hydroaminoalkylation with good to complete control of anti-diastereoselectivity (Scheme 18).…”
Section: Hydroaminoalkylationmentioning
confidence: 58%
“…98 Whereas ruthenium(II) catalysts promote hydroaminoalkylation through hydrometalative pathways, ruthenium(0) catalysts derived from Ru 3 (CO) 12 and triphos enable catalytic mechanism involving diene-imine oxidative coupling (Scheme 20). 99 Presently, transformations of this type are restricted to the hydroaminoalkylation of isoprene with aryl substituted hydantoins. The catalytic mechanism involves hydrogenolytic cleavage of the azaruthenacyclopentane intermediate through hydrogen transfer from the hydantoin reactant, which releases product and regenerates the requisite imine for oxidative coupling.…”
Section: Hydroaminoalkylationmentioning
confidence: 99%
“…6 Very recently, the linear prenylation of imines has also been accomplished under transfer hydrogenation conditions. 7 Surprisingly, to our best knowledge, only one example of α-prenylation of imines with moderate enantioselectivity (80:20 er) has been reported to date.…”
Section: Introductionmentioning
confidence: 99%